Isolation and Characterization of Xylanase from a Novel Strain, Penicillium menonorum SP10 - Thi Thu Huong Luong; Supattra Poeaim; Narumon Tangthirasunun (Mycobiology, 2023)
SP10 as a good candidate for industrial uses, especially in poultry feed and pulp industries, to improve yield and economic efficiency under slightly acidic and high-temperature conditions.
Keywords: Biofuel production and bioconversion; Studies on Chitinases and Chitosanases; Enzyme Production and Characterization